Attention to body parts prompts thermoregulatory reactions in Body Integrity Dysphoria. (February 2022) - Salvato, Gerardo; Zapparoli, Laura; Gandola, Martina; Sacilotto, Elena; Ludwig, Nicola; Gargano, Marco; Fazia, Teresa; Saetta, Gianluca; Brugger, Peter; Paulesu, Eraldo; Bottini, Gabriella
Abstract: In healthy subjects, the transient perturbation of body part ownership is accompanied by regional skin temperature decrease. This observation leaves an open question about a possible body part-specific thermoregulatory response in pathological conditions, in which the sense of ownership over that body part is altered. For instance, Body Integrity Dysphoria (BID), a poorly understood neuropsychiatric disorder, is characterised by the non-acceptance of one or more of one's extremities. This unsettling feeling pervasively captures the individuals' attention towards the unwanted limb. Previous studies characterised BID in terms of absent ownership feeling with preserved ownership judgment. We explored for the first time whether this altered feeling is also associated with a specific thermoregulatory response. We recorded thermal image sequences of circumscribed regions of the limbs' skin in seven individuals with BID desiring to remove one leg while they were invited to focus their attention toward one particular limb (arm or leg). Their event-related thermoregulatory pattern was compared to a group of healthy matched controls. In individuals with BID but not in control persons, we found a bilateral decrease in leg temperature when focusing their attention on either the unwanted or accepted leg. The event-related thermoregulatory response for both upper limbs was similar between individuals with BID and healthy controls. Our results suggest that the alteration of the sense of body ownership in neuropsychiatric conditions such as BID may critically rest on specific event-related thermoregulatory patterns in response to modulation of attention to body parts.